Dye‐Controlled Interfacial Electron Transfer for High‐Current Indium Tin Oxide Photocathodes1. Issue 23 (23rd April 2015) - Huang, Zhongjie; He, Mingfu; Yu, Mingzhe; Click, Kevin; Beauchamp, Damian; Wu, Yiying
Abstract: Efficient sensitized photocathodes are highly desired for solar fuels and tandem solar cells, yet the development is hindered by the scarcity of suitable p‐type semiconductors. The generation of high cathodic photocurrents by sensitizing a degenerate n‐type semiconductor (tin‐doped indium oxide; ITO) is reported. The sensitized mesoporous ITO electrodes deliver cathodic photocurrents of up to 5.96±0.19 mA cm −2, which are close to the highest record in conventional p‐type sensitized photocathodes. This is realized by the rational selection of dyes with appropriate energy alignments with ITO. The energy level alignment between the highest occupied molecular orbital of the sensitizer and the conduction band of ITO is crucial for efficient hole injection. Transient absorption spectroscopy studies demonstrate that the cathodic photocurrent results from reduction of the photoexcited sensitizer by free electrons in ITO. Our results reveal a new perspective toward the selection of electrode materials for sensitized photocathodes. Abstract : ITO as a photocathode : The scarcity of optimal p‐type semiconductors has hindered the development of efficient photocathodes for dye‐sensitized solar cells and photoelectrosynthesis cells. Mesoporous indium tin oxide (ITO), an n‐type degenerated semiconductor, can generate remarkably high cathodic currents after sensitization by energy‐aligned cyclometalated Ru II complexes. Studies into the mechanism indicate hole injection from the excited dye.